Analisis Informasi Perbankan Syariah dalam Upaya Mengembangkan Syariah di Indonesia - Ali Mahadi Ritonga (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Strategic in people's economic development, contributing to economic transformation in productive, value-added and inclusive economic activity. However, in the era of digital finance and the high competition in the financial services industry as it is today, Islamic banking faces various challenges, especially related to the low is one of the roles of the Islamic Banking industry to have Information and Communication Technology (ICT) and limited capital. Therefore, the Islamic banking industry must take advantage of various opportunities, namely by providing innovative products based on Information and Communication Technology (ICT) to provide a variety of choices and expand reach to the public. However, until now the innovation of Islamic banking products is still very limited. In addition, another thing that is no less important to support the development of Islamic Banking in Indonesia is to take advantage of economic growth opportunities, and increase the availability of Islamic bank funds. By taking advantage of this opportunity, the Islamic banking industry in Indonesia can develop and have competitiveness.